THE RELATIONSHIP OF NUTRITION KNOWLEDGE, FREQUENCY OF ILLNESS AND ECONOMIC STATUS WITH THE INCIDENCE OF STUNTING IN THE WORKING AREA OF THE TANAH KALI KEDINDING SURABAYA HEALTH CENTER - Astrida Budiarti; Savira Adella Fitria Putry (International Journal of Nursing and Midwifery Science (IJNMS), 2025)
Stunting is a chronic nutritional problem caused by inadequate nutritional intake for a long time due to a lack of knowledge of mothers in feeding toddlers so that they are not in accordance with the nutritional needs needed. The purpose of this study was to analyze the relationship between knowledge, illness frequency and economic status with the incidence of stunting in the working area of the Tanah Kali Kedinding Health Center. The research method is a correlation analytic study with a cross-sectional approach. The research location was at Tulip and Melati Putih Tanah Merah Utara Posyandu. The sampling technique used an purposive sampling sample of 111 toddlers aged 2-5 years. The research instrument was a questionnaire containing knowledge of toddler nutrition, illness frequency and economic status as well as observations using a microtoise. Data were analyzed by Chi Square test. The results of the study show that there is a relationship between nutritional knowledge and the incidence of stunting and there is no relationship between the frequency of illness, economic status and the incidence of stunting. Chi Square test results showed knowledge p=0.001 (p-value<0.05), frequency of illness p=0.734 (p-value<0.05), economic status p=0.306 (p-value<0.05). The implication of this study is that the level of maternal nutrition knowledge influences attitudes and behavior in choosing food, cadres as the representative of health workers in the community are advised to provide counseling and education using various methods such as videos, leaflets and other media on maternal knowledge regarding balanced nutrition and stunting.